Rekonstrukce městského úřadu v Radnicích - Štrunc, Michal (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Diplomová práce se zabývá projektovou dokumentací rekonstrukce polyfunkčního domu v Radnicích, který je navržen jako čtyřpodlažní. V prvním nadzemním podlaží jsou prostory České pošty a lékárny. Druhé a třetí nadzemní podlaží je určeno pro správu obce a ve čtvrtém nadzemním podlaží je městská knihovna. Konstrukční systém je monolitický rámový skelet se stropními panely a sedlovou střechou. Objekt se nachází v řadové zástavbě na náměstí.

This diploma thesis deals with the project documentation of the reconstruction of a mixed-use building in Radnice, which is designed as a four-floor. In the first floor are premises of a post office a pharmacy. The second and the third floor is designed for the management of the city and there is a public library in the fourth floor. The structural system is a cast-in-place concrete frame with the precast floor slabs and the gabled roof. The building is located in a terraced house on a square.
Reconstruction of the Municipal Authority in Radnice
Keywords: projektová dokumentace; rekonstrukce; Česká pošta; lékárna; radnice; podlaží; řadová zástavba; knihovna; monolitický skelet; project documentation; reconstruction; post office; pharmacy; municipal authority; floor; terraced house; public library; cast-in-place concrete frame